(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the development of digital pedagogical skills among future primary school teachers. It discusses the relevance of digital tools in primary education, identifies key challenges in their application, and suggests practical solutions for improving their effective use.